Challenges in disclosure of adverse events and errors in surgery; perspectives from sub-Saharan Africa - Ibrahim, Abdulrasheed; Ekundayo, Stephen Garba; Eneye Asuku, Malachy (Pan African Medical Journal, 2012)
Surgery in sub-Saharan Africa is widely known to be done against a background of poverty and illiteracy, late presentation with complicated pathologies, and a desperate lack of infrastructure. In addition, patient autonomy and self determination are highly flavored by cultural practices and religious beliefs. Any of these factors can influence the pattern and disclosure of adverse events and errors. The impact of these in the relationships between surgeons and patients, and between health institutions and patients must be considered as it may affect disclosure and response to errors. This article identifies the peculiar socioeconomic and cultural challenges that may hinder disclosure and proposes strategies for instituting disclosure of errors and adverse events services in Sub-Saharan Africa
Keywords: Challenges; Adverse events; Surgery; sub-Saharan Africa